Dynaclose Tape: A Practical Alternative to Punch Biopsy Site Closure. Issue 1 (January 2013) - Doumit, Joseph; Vale, Rachel; Kanigsberg, Nordau
Background: A punch biopsy is a common therapeutic and diagnostic procedure that is routinely performed by dermatologists. A thin cylinder of tissue is removed with a biopsy punch, which creates a full-thickness wound. Sutures are used for primary closure as part of standard practice and are removed in follow-up 5 to 14 days later. The biopsy site heals with a small linear scar. In the past, punch biopsies were often left to heal by secondary intention, but given the extended healing time, this has fallen out of practice among dermatologists. Objective: The purpose of this case report is to introduce a new quick and cost-effective approach to accelerate secondary intention healing following punch biopsies in busy dermatology clinics. Results/Conclusion: We present a case where Dynaclose tape (Canica Design Inc, Almonte, ON) was used as an alternative to sutures for biopsy site closure. Dynaclose tape is a strip with adhesive ends and a clear center composed of silicone elastomer. The silicone elastomer promotes wound closure by pulling the opposing margins together. The tape maintains excellent adhesion and follows the natural shape of the skin to maximize patient comfort and mobility.